High complete resection rate for pre-lift and cold biopsy of diminutive colorectal polyps - O’Connor, Sam A.; Brooklyn, Trevor N.; Dunckley, Paul D.; Valori, Roland M.; Carr, Ruth; Foy, Chris; Somarathna, Thusitha; Adamczyk, Lukasz A.; Shepherd, Neil A.; Anderson, John T. (Endoscopy International Open, 2018)
Background and study aims The majority of polyps removed at colonoscopy are diminutive (≤ 5 mm) to small (< 10 mm) and there are few guidelines for the best way for these polyps to be removed. We aimed to assess the feasibility and effectiveness of cold biopsy forceps polypectomy with pre-lift (CBPP) for polyps ≤ 7 mm. Our aims were to assess completeness of histological resection of this technique, to identify factors contributing to this and assess secondary considerations such as timing, retrieval and complication rates.Patients and methods We conducted a prospective cohort study on consecutive patients receiving a colonoscopy at Cheltenham General Hospital, as part of the National Bowel Cancer Screening Program (BCSP) in England. The study included only polyps that were judged as ≤ 7 mm by the colonoscopist. A small sub-mucosal pre-lift injection was administered prior to removal of the polyp using cold biopsy forceps. One or more biopsies were taken until the polyp was confidently assessed visually as being completely removed by the colonoscopist. The entire polypectomy site was then removed en bloc by endomucosal resection (EMR) with a margin of at least 1 to 2 mm around defect. This was sent for histopathological analysis to assess completeness of resection. Polypectomy timing, tissue retrieval, number of bites required for visual resection and complications were recorded at the time of the procedure.Results Sixty-four patients were recruited and consented. Of them, 42 patients had a total of 60 polyps resected. Three patients had inflammatory polyps and were excluded from the study, leaving 57/60 polyps for final analysis. Seventeen were hyperplastic and 40 adenomatous polyps. Retrieval was complete for all 57 polyps and there were no complications both during or post- polypectomy. The complete resection rate (CRR) was 86 %. The technique was more effective in smaller polyps with 91.7 % of diminutive polyps (≤ 5 mm) completely excised. Conclusions CBPP is a safe and highly effective technique for polyps < 5 mm with a high complete resection and retrieval rate. The time taken for the procedure is significantly greater than cold forceps alone, or cold snare as seen in other studies.